Teaching Materials of Thematic Learning Model Based on Innovative Models to Develop Teaching Ability of Primary School Students - Usman, Nuraini; Raharjo, Makmum; Pulungan , Marwan; M Sofwan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Education has a great influence on the applicable curriculum. The objectives of this research are (1) to produce teaching materials that can be used in making elementary thematic devices at PGSD FKIP Universitas Sriwijaya; (2) describe the results of the product feasibility of teaching materials for elementary thematic learning. This development research is expected to have benefits in helping students understand the thematic learning lecture material for elementary schools contained in courses from various subjects in elementary school by applying various innovative learning models that are appropriate and can be applied in elementary schools later. The device development model used in this study is a model adapted from the 4D development model which consists of 4 stages, namely 1) the define 2) the design 3) the develop 4) the disseminate. Data collection techniques are expert validation sheets and questionnaires. Data analysis used qualitative analysis and analysis of expert validation test results. The product trial phase was carried out on 7th semester students. Based on the results of student responses to the developed teaching materials, it was very good, with an average percentage score of 84.25%. From the research results, the development of thematic learning skills with this innovative model is very useful in shaping the character of prospective elementary school teachers and also in responding to the development of globalization.